Interpreting Melville’s Typee: a Victorian age journey to understanding savage and civilized societies - Wan Yahya, Wan Roselezam; Taha, Susan (Universiti Putra Malaysia Press, 2013)
Herman Melville’s novel, Typee: A Peep at Polynesian Life, is said to depict common travel writing themes such as confusion, discomfort, discovery and natural beauty. However, a more careful examination of the text reveals that there are strong social critiques of racism and imperialism and a struggle with what makes humans civilized beings or savages. The issue of cannibalism haunts the story, as do the abusive practices of colonial and whaling-ship officers, which provides the necessary suspense to carry the reader through the story to its end. Cannibalism as a cultural practice is explained according to the social and political context of contact with European aggression and devastation. By analysing the text using the concepts of hegemony and binary opposition, it is clear that Melville challenges the narrative that South Pacific natives were savage cannibals inferior to civilized Europeans. He shows that the apparent savage aggressiveness of the Typees and other South Pacific islanders, was not inherent to their culture but was provoked by attacks from outsiders, particularly Europeans and Americans.